Serum ferritin levels and endocrine disorders in children with thalassemia major - Evi Dewiyanti; Aditiawati Aditiawati; Dian Puspita Sari (Indonesian Pediatric Society, 2021)
Background Endocrine disorders in thalassemia major children patients occur due to iron overload and hemosiderosis in endocrine organs. Early detection is needed to prevent complications and improve the quality of life. An association between serum ferritin and endocrine disorders in thalassemia patients has been inconclusive to date. Objective To analyze for possible associations between serum ferritin and endocrine disorders (short stature, delayed puberty, delayed bone age, hypothyroidism, impaired glucose tolerance, and diabetes mellitus) and the incidence of each disorder in thalassemia major. Methods There were 115 thalassemia major patients aged 10-18 years involved in our cross-sectional study from June 2019 - June 2020 in the Pediatrics Department, DR. M Hosein Hospital, Palembang, South Sumatera. Anthropometry and socioeconomic status informations were collected from physical examination and interview. Ferritin, FT4, TSH, Hb and glucose levels measured by using standard methods for each item in the laboratory, mean while the skeletal age assessment was determined by using FELS method. Results This study included 83 (72.2%) girls and 32 (27.8%) boys. There were 89 (77.4%) subjects with short stature, 74 (64.4%) with delayed bone age, 30 (26.1%) with impaired glucose tolerance, 25 (21.7%) with delayed puberty, 4 (3.5%) with diabetes mellitus (DM), and none with hypothyroidism. Bivariate and multivariate analyses revealed no associations between serum ferritin and short stature, delayed bone age, impaired glucose tolerance, delayed puberty, and DM. Conclusion There is a high prevalence of endocrine disorders in pediatric thalassemia patients, especially short stature and delayed bone age. However, there are no associations between serum ferritin and endocrine disorders in these patients.